(untitled) (Architecture Image Studies, 2025)
It has been 82 years since the first publication of Islamic studies in Scopus indexed journal. Today there is a total of 1033 documents published in the scientific database, and it is interesting to see how the discussions within the field have been developing over time. Using the combination of the biblioshiny package in Rstudio and the VOSviewer, this study found that Tottoli leads the greatest number of publications in Islamic studies, the country analysis revealed that the USA publishes the most, Journal of Qur’anic Studies is leading in terms of Scopus indexed journals, and Islamic education has been the topmost in terms of keyword statistics analysis. It concluded that Islamic studies as a research topic has been continuously rising to date and Islamic education among others is gaining so much attention among writers in the scientific literature. In conclusion, this study empirically revealed the dynamism of Islamic studies in terms of individual brilliance, national engagement, textual relevance, and the rising focus on education as the trajectory of Islamic studies.